The Beach as a Tourist Commercial Use in Mexico. Comparative Study Mazatlán-Acapulco - Sonda de la Rosa, Ricardo (Corporación Universitaria del Caribe, CECAR., 2021)
According to Richard Butler’s theory on the life cycle of tourist destinations, the objective of the research is to make an inventory and compare the tourist businesses between two Mexican destinations. A mixed approach is applied through a case study methodological strategy, addressing qualitative aspects with phenomenological research. Commercial activities, that satisfy the requirements and expectations of tourists on the selected tourist beaches, were recorded, classified and compared. In the results section, the similarities and differences in the tourist businesses carried out are outlined, which will serve as input for future decision-making in matters of innovation and industrial strengthening of the products and services, offered and demanded.